2020
DOI: 10.1016/j.seizure.2019.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Predicting first attendance at psychiatry appointments in patients with dissociative seizures

Abstract: Patients with dissociative (non-epileptic) seizures typically receive their diagnosis from neurologists, but are often referred to psychiatrists, whom they may be reluctant to go and see. We aimed to assess which factors were associated with first attendance at psychiatric services. Methods: A cohort study of 698 participants involved in the pre-randomisation phase of the CODES trial, a randomised controlled trial assessing the benefit of cognitive behavioural therapy for dissociative seizures when added to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…Considering patients’ preferences, treatment recommendations were discussed with the majority of patients who were not already receiving any treatment and follow-up yielded high adherence rates in epilepsy and PNES patients (94 and 100%). In comparison to other studies the initial adherence to therapeutic recommendations in this study is high, particularly in PNES patients ( Goldstein et al, 2020 ; Stone et al, 2020 ). Previous studies have demonstrated the clinical relevance of strengthening patient motivation when discussing therapeutic recommendations with PNES patients ( Tolchin et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 66%
“…Considering patients’ preferences, treatment recommendations were discussed with the majority of patients who were not already receiving any treatment and follow-up yielded high adherence rates in epilepsy and PNES patients (94 and 100%). In comparison to other studies the initial adherence to therapeutic recommendations in this study is high, particularly in PNES patients ( Goldstein et al, 2020 ; Stone et al, 2020 ). Previous studies have demonstrated the clinical relevance of strengthening patient motivation when discussing therapeutic recommendations with PNES patients ( Tolchin et al, 2019 ).…”
Section: Discussioncontrasting
confidence: 66%
“…Although we did not collect detailed data about psychiatric comorbidity on the 698 people initially entering the study, basic demographics of the cohort ( N = 368) reported here were similar to the larger group of 698 patients initially recruited into the CODES study (Goldstein et al, 2019). Furthermore, the generalisability of the sample reported here is supported by the observation that there were no significant differences in clinical and demographic variables between 568 of this initial group who attended a psychiatric assessment (and whose further eligibility was therefore considered for the RCT), compared to 130 who did not (Stone et al, 2020). In addition, we have recently shown (Goldstein et al, in press) that the 368 people reported here did not differ on key characteristics from the 58 people eligible for the RCT but who ultimately did not participate (see Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Characteristics of the 698 for whom baseline assessments were collected for Phase 1 have been reported by Goldstein et al (2019). In addition, variables predicting which of the 698 participants did not attend psychiatry appointments have been reported by Stone et al (2020). …”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…These classic obstacles are also found at an international level, with even greater difficulties in the poorer countries [20]. A recent cohort study [21] showed that a first attendance at a psychiatry appointment after a diagnosis of PNES delivered by was not associated with any predictors, including patient confidence in the diagnosis.…”
Section: Consensual Withdrawalmentioning
confidence: 99%